(untitled) (Journal of Chemical Engineering, 2014)
Potato snack is one of the most popular snacks item in Bangladesh. In this study the nutrition facts of potato snacks (potato chips and french fries) of different brands of home and aboard and of different food chain shops were analyzed and compared with the ideal one. From this study it was observed that most of the brands have been deviated from the quantity of nutrition facts that should be contained in an ideal potato snack. The noteworthy difference was noticed for the case of protein content for potato chips. For French fries, it has been determined that homemade french fries contain the lowest fat and carbohydrate. Since potato snacks are a source of harmful trans-fat, saturated fat and also high in calories, this paper has been discussed some healthier alternatives to this salty snack such as baked potato snack, using sugar solution and sweet potato. DOI: http://dx.doi.org/10.3329/jce.v28i1.18102 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 4-8